Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1021/bi00094a020
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the Xenopus laevis B.beta. fibrinogen subunit gene by glucocorticoids and hepatocyte nuclear factor 1: Analysis by transfection into primary liver cells

Abstract: The blood-clotting protein fibrinogen is composed of three subunits, designated A alpha, B beta, and gamma, which are encoded by a family of related genes. As part of the acute-phase response, expression of the fibrinogen genes is coordinately regulated in the liver by glucocorticoids. To understand the factors underlying this hormonal response, we have examined control of transcription from fibrinogen gene fragments transfected into hepatocytes from the frog Xenopus laevis. This analysis is the first in any s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…A second consequence of HNF4 expression in H5 cells is the reexpression of a subset of genes whose expression is characteristic of hepatocytes and of well-differentiated cells of the H4II lineage. The genes coding for ␣1-AT, ␤Fib, and TTR all possess well-characterized HNF4 or HNF1 binding sites in their regulatory regions (18,33,50). Since both the ␣1-AT and ␤Fib genes are weakly expressed in H5 cells subjected to longterm DEX treatment, both genes posses the potential to be expressed: the presence of HNF4tag and HNF1 permits real-ization of this potential.…”
Section: Phenotypic Consequences Of Expression Of Hnf4mentioning
confidence: 99%
“…A second consequence of HNF4 expression in H5 cells is the reexpression of a subset of genes whose expression is characteristic of hepatocytes and of well-differentiated cells of the H4II lineage. The genes coding for ␣1-AT, ␤Fib, and TTR all possess well-characterized HNF4 or HNF1 binding sites in their regulatory regions (18,33,50). Since both the ␣1-AT and ␤Fib genes are weakly expressed in H5 cells subjected to longterm DEX treatment, both genes posses the potential to be expressed: the presence of HNF4tag and HNF1 permits real-ization of this potential.…”
Section: Phenotypic Consequences Of Expression Of Hnf4mentioning
confidence: 99%
“…This holds true also for fibrinogen genes. In Xenopus laevis, a single GRE at bases -148 to -162 of the ␤ fibrinogen gene is present (28), while glucocorticoid regulation of the ␥ fibrinogen gene requires at least three nearby GREs and an accessory factor binding site, all within the first 187 bp of the promoter (34). In the human ␥ fibrinogen gene, we have shown that a GRE at position -1116 to -1102 confers dexamethasone inducibility.…”
Section: Discussionmentioning
confidence: 82%
“…The value for Bβ-136 represents a non-induced baseline from a construct previously shown to be unresponsive to glucocorticoids (19). The percentages from six to ten experiments were averaged and the standard error of the mean (SEM) was calculated.…”
Section: Luciferase and β-Gal Reporter Assaysmentioning
confidence: 99%